2019
DOI: 10.1186/s12887-019-1865-0
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and neonatal factors involved in the development of childhood allergic diseases in Guangzhou primary and middle school students

Abstract: BackgroundAllergic diseases, such as asthma, dermatitis, rhinitis, and eczema, are highly prevalent in Chinese school children. Environmental factors, including air pollution and automobile exhaust, play an important role in the etiology of these diseases. However, prenatal and neonatal factors, such as gender, maternal diseases during pregnancy, and premature birth, may also be associated with allergic disease occurrence. The objective of this study was to explore prenatal and neonatal factors that are involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
3
15
2
1
Order By: Relevance
“…Our findings are consistent with most previous studies in which CS delivery, only one child in the household and formula feeding were associated with an increased risk of allergic diseases among children [ 6 8 , 12 18 ]. Recently, a systematic review and meta-analysis reported that male sex, short duration of breastfeeding and having siblings were risk factors of early transient wheezing among children aged 3–18 years [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent with most previous studies in which CS delivery, only one child in the household and formula feeding were associated with an increased risk of allergic diseases among children [ 6 8 , 12 18 ]. Recently, a systematic review and meta-analysis reported that male sex, short duration of breastfeeding and having siblings were risk factors of early transient wheezing among children aged 3–18 years [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…Mounting evidence suggests that prenatal and neonatal factors are associated with the development of childhood asthma and allergic diseases [6][7][8]. In China, a study conducted in Guangzhou, China found that male sex, high birth weight, cesarean section (CS) delivery, and only one child in the household were associated with the risks of allergic diseases in children aged 6-18 years [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ndings are consistent with most previous studies in which CS delivery, only one child in the household and formula feeding were associated with an increased risk of allergic diseases among children [6][7][8][12][13][14][15][16][17][18]. Recently, a systematic review and meta-analysis reported that male sex, short duration of breastfeeding and having siblings were risk factors of early transient wheezing among children aged 3-18 years) [19].…”
Section: Discussionsupporting
confidence: 92%
“…Mounting evidence suggests that prenatal and neonatal factors are associated with the development of childhood asthma and allergic diseases [6][7][8]. In China, a study conducted in Guangzhou, China found that male sex, high birth weight, cesarean section (CS) delivery, and only one child in the household were associated with the risks of allergic diseases in children aged 6-18 years [8]. Another study in Shanghai found that CS without medical indication was associated with increased risks of both childhood asthma and AR, and breastfeeding in early infancy attenuated these risks [6].…”
Section: Introductionmentioning
confidence: 99%